An analysis of the tourism curriculum at Boland College : what the tourism industry in Stellenbosch requires from entry level college employees - Swart, Claudia (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.